Cyber Terrorism Countermeasures in Indonesia - Saptaning Ruju Paminto (Jurnal Wawasan Yuridika, 2022)
The crime of terrorism is classified as an extraordinary crime, along with various other forms of radicalism. Recent acts of terrorism are suspected to be the result of massive activism from cyberspace. The purpose of this study is to examine efforts to counter cyber terrorism. This research is descriptive with normative juridical research type, using literature studies through a theoretical approach, and then the data is analyzed qualitatively. The results of this study were coordinating actions by making agreements with other countries related to cyber terrorism crimes (including information exchange and creating data centres on Indonesia's servers to prevent cyber-terrorist operations), with efforts to prevent and eradicate cyber terrorism activities need a lot of cooperation, both with domestic and international stakeholders.